EL "OTRO" MÉXICO FORESTAL (LA ACTIVIDAD FORESTAL ILÍCITA) - Caballero Deloya, Miguel (Revista Mexicana de Ciencias Forestales, 2020)
Forestry in Mexico moves along two main economic avenues. One is illegal and lacks of statistics. lt is well recognized however, and has important ecological, social and economic impact. lllegality in Mexican forestry has been growing, demonstrating society and governmental incompetence for its fight against. lts success is based in the efficient operation of the illegal production chain, whose links are: a) illegal log harvesting; b) Transport of illegal logs; e)lndustrialization of illegal logs and (d) Commercialization of products from illegal logs. The historie incompetence of the government to fight forestry illegality is due to: 1) non applied or inappropriately or discretionally applied legislation; 2)limited, inefficient forest services operating with poor financing, high bureaucracy and corruption; 3) centralized, scarcely applied and continuously changing public policies, made by bureaucrats disconnected from reality. Given the invaluable importance of forest resources to society, it is recommended to fight forest illegality as a national crusade, with adequate financing, entirely transparent process, based on a close follow up on the four links of the forest production chain, in addition to promoting and awarding the legal forest activity.